Biological Safety in Russia: Ethical Issues - K. S. Litovko (Теоретическая и прикладная юриспруденция)
The purpose of the work was to consider in the article certain features of ensuring biological safety in the Russian Federation, legal novelties in this area, general trends, analysis of possible identified problems. With the help of general philosophical methods, as well as with the help of the formal legal method, the ethical aspect of ensuring biological safety in the context of countering the COVID-19 pandemic was investigated. The general characteristics of bioethics and its principles are given, individual political decisions and regulations are analyzed in the context of these principles. According to the results of the study, it is concluded that there are problems in compliance with the principles of bioethics during the period of countering COVID-19, these problems are listed and commented on.